(untitled) (Asian Journal of Social Science Studies, 2026)
World War II (WW II) has been the most destructive war the mankind has ever experienced. It has started in Europe like World War I (WW I), most of fighting went on in Europe, but it has spread to North Africa and Far East. The estimated causalities are around 60 million people, 60 % of them being civilians. The devastating results of the war inevitably caused major global changes. The two opposing ideologies, capitalism and communism, practically divided the political arena into two blocks under the leadership of United States and Soviet Union. United Nations has been established with the purpose of solving problems by negotiations and maintaining world peace. The bipolar political status often referred to as “cold war” has lasted more than four decades ending with fall of Berlin wall and disintegration of Soviet Union. Turkey’s position both during WW II and postwar era has been crucial in the history of the young Republic.